(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Introduction: Bronchogenic cysts are congenital anomalies caused by abnormal bronchial development from the primitive ventral foregut, which arises from cells isolated from the main pulmonary branching when lung bud separates from the primitive gut. Materials & Methods: We reviewed all pediatric patients with bronchogenic cyst who underwent surgery in our thoracic surgical unit- III during 2007-2009. They comprised 1 male and 5 female patients, with an age range of 2 to 17 years (mean age 5.66 years). Results: Symptoms were present in 5 patients (83%), cough was the most common symptom. Other symptoms included purulent sputum, chest pain, fever, dyspnea, anorexia and/or weight loss, and haemoptysis. All patients underwent chest x-ray posteroanterior and lateral view and CT scan of chest for diagnostic purpose. Two of the cysts were mediastinal and rests were intraparenchymal. Surgery performed were resection (2), lobectomy (4). Complications of bronchogenic cysts occurred in 4 patients (67%). In 1 patient (Patient 2), a ruptured, infected, parenchymal bronchogenic cyst caused pleuritis and empyemaThere was no operative deaths & no in-hospital mortality. Conclusions: We conclude that one should go for surgical resection of all suspected bronchogenic cysts in operable candidates. DOI: http://dx.doi.org/10.3329/jpsb.v1i2.19524